2022
DOI: 10.1016/j.ccc.2022.01.006
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Nasal Oxygen and Noninvasive Ventilation for COVID-19

Abstract: High-flow nasal oxygen (HFNO) and non-invasive ventilation (NIV) via face-mask or helmet have been increasingly used in the management of acute hypoxemic respiratory failure (AHRF) due to COVID-19 with the premise of reducing the need for invasive mechanical ventilation and possibly mortality. However, their use carries the risk of delaying intubation and nosocomial infection transmission. To this date, most studies on the effectiveness of these modalities are observational and suggest that HFNO and NIV have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…23 HFNO and NIV are the main methods used for management of hypoxemic acute respiratory failure, and many clinical studies have shown that they are associated with good results in patients with COVID-19, lowering the need for invasive mechanical ventilation and the mortality rates. [24][25][26] However, a 2022 study showed that NIV was associated with higher mortality and intubation rates compared with HFNO and continuous positive airway pressure (CPAP). 27 A meta-analysis of 58 studies concluded that there is no consensus regarding the use of noninvasive respiratory support and that the information about the indications for initiation or suppression of these therapies is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 HFNO and NIV are the main methods used for management of hypoxemic acute respiratory failure, and many clinical studies have shown that they are associated with good results in patients with COVID-19, lowering the need for invasive mechanical ventilation and the mortality rates. [24][25][26] However, a 2022 study showed that NIV was associated with higher mortality and intubation rates compared with HFNO and continuous positive airway pressure (CPAP). 27 A meta-analysis of 58 studies concluded that there is no consensus regarding the use of noninvasive respiratory support and that the information about the indications for initiation or suppression of these therapies is unclear.…”
Section: Introductionmentioning
confidence: 99%
“… 23 HFNO and NIV are the main methods used for management of hypoxemic acute respiratory failure, and many clinical studies have shown that they are associated with good results in patients with COVID-19, lowering the need for invasive mechanical ventilation and the mortality rates. 24 26 However, a 2022 study showed that NIV was associated with higher mortality and intubation rates compared with HFNO and continuous positive airway pressure (CPAP). 27 …”
Section: Introductionmentioning
confidence: 99%